Obligate parasitic fungi of Tuzlovski lymany National Nature Park (Odessa region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Study of obligate parasitic fungi in the territory Tuzlovski lymany National Nature Park (Odessa region, Ukraine) resulted in the detection of 40 species of the orders Albuginales (one species), Erysiphales (12), Peronosporales (6) and Pucciniales (21). 31 species are new for the territory of park. Rust fungus Uromyces aeluropodis-repentis is reported for the first time in the territory of Right Bank Steppe of Ukraine, species Erysiphe buhrii, Peronospora holostei, Puccinia liliacearum, Uromyces giganteus та U. polycnemi are rare for the Right Bank of Steppe zone and Ukraine. Identified fungi parasitized 51 species of host plants belonging to 44 genera and 26 families. Among plants Thlaspi perfoliatum is new for Ukraine host of Albugo candida and two species – Ornithogalum boucheanum and Trachomitum sarmatiense listed in the Red Book of Ukraine (2009).
Keywords: obligate parasitic fungi, host-plants, Tuzlovski lymany National Park.